Islamic bank stability - initial evidence / Mohd Afandi Abu Bakar, AP Dr. Mohd Fauzi Mohd Harun and AP Dr. Abdul Malek A Tambi - Abu Bakar, Mohd Afandi; Mohd Harun, Mohd Fauzi (AP Dr.); A Tambi, Abdul Malek (AP Dr.) (2013)
Stability of the banking sector is one of the most important features that support and contribute to continuous economic expansion and development. It will facilitate and smooth the flow of funds across the economic units more efficiently and effectively. This study examines the stability of Islamic banks. The study employs an unbalanced panel data analysis on the annual growths of 67 Islamic banks from various countries for the period spanning from 1998 to 2009. The finding provides some evidence on the stability of Islamic bank operations. The growth of Islamic bank financing is independent of the growth of business cycle indicators, thus, free from any speculative activities. Hence, the behaviour of the Islamic bank was not that enthusiastic to the movement in economic environment ffuctuaticns. Although the contingency reserve and provision for loan losses are able to control the financing activities from behaving pro-cyclically, the finding also shows that Islamic banks need to observe its management of contingency reserves and provision for loan losses. The amount is still not large enough to manage the earning assets that have a direct influence on the financing volume. This is evidence from the insignificant relationship of financing growth of Islamic bank to the real GDP growth, money supply M2 growth and the CPI growth. Therefore, the policy on contingency reserves and provision for loan losses needs some serious consideration from the Islamic bank management so that it will also be able to confirm the capability of Islamic bank to work as the transmitter mechanism of monetary policy.